2010
DOI: 10.1111/j.1756-185x.2009.01455.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the International Criteria for Behçet’s disease (ICBD) in Iran

Abstract: ICBD has by far better performance than ISG in Iran. The difference is even more prominent in Iranian patients than in the cohort of the international patients upon whom the criteria were created.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 11 publications
1
45
0
2
Order By: Relevance
“…A total of 100 points or more classify the patient as having BD. The sensitivity of Hewitt was very low and the specificity very high [2,3].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…A total of 100 points or more classify the patient as having BD. The sensitivity of Hewitt was very low and the specificity very high [2,3].…”
mentioning
confidence: 95%
“…A patient who has 3 major or 2 major and 2 minor manifestations is classified as BD. Mason and Barnes criteria have low sensitivity and high specificity [2,3,7,8].…”
mentioning
confidence: 99%
“…дополнены сосудистыми поражениями, которые характер-ны для болезни Бехчета: поверхностный флебит, тромбоз глубоких вен, тромбоз крупных венозных сосудов, арте-риальные тромбозы и аневризмы [23]. ICBD-критерии подчеркивают диагностическую значимость при болезни Бехчета оральных, генитальных язв и поражений глаз.…”
Section: Introductionunclassified
“…In 2010, Davatchi et al [13] evaluated the ICBD's performance in Iran on a large cohort from their BD registry (6,128 patients), with 3,400 controls. They reported that the ICBD outperformed the ISG criteria on all fronts, with a higher sensitivity (98.2%), specificity (95.6%) and accuracy (97.3%), while comparatively the ISG criteria held low sensitivity (78.1%), high specificity (98.4%) but only 85.5% accuracy.…”
Section: The International Criteria For Behçet's Diseasementioning
confidence: 99%